Fabrication of Si tunnel diodes for c-Si based tandem solar cells using proximity rapid thermal diffusion. (September 2017) - Fave, Alain; Lelièvre, Jean-François; Gallet, Thibaut; Su, Qiaoyu; Lemiti, Mustapha
Abstract: Increasing competitiveness of photovoltaic (PV) devices is currently an important objective in technological research, especially with the development of tandem solar cells based on c-Si as the bottom cell. For a monolithical structure, a tunnel diode in between the top and bottom cells is necessary. In this work we report on the development of the fabrication of Si tunnel junction using a combination of spin-on doping and proximity rapid thermal diffusion. A desirable attribute of this process is simplicity. Two different structures p ++ /n ++ or n ++ /p ++ were fabricated on (100) Si substrates. Carrier density profiles were measured by ECV to characterize the shallow doping profiles. Vertical tunnel diodes were fabricated and I(V) characteristics are presented. It is shown that device peak current densities up to 270 A/cm² are achieved using this technique, which is the best value reported with such simple technique.